Pengaruh Penerimaan Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (Pad) Kota Madya Bandung - Ma'arif, Muhammad Iqbal; Afriady, Arif (Indonesian Accounting Research Journal, 2025)
The study aim how of realization local tax revenue with the realization of retribution revenue affect revenue (PAD) in Bandung Government for 2016-2022. The research is quantitative study with secondary data from Bandung City Regional Revenue Agency. Multiple linear regression analysis are the analysis technique used with the SPSS 25.This study indicate that result of local taxes have a positive effect on local revenue in Bandung City from the significance of local taxes 0.001. the significance value is 0.194 for retribution does’nt have a positive impact on local revenue (PAD) in Bandung. However, simultaneously local retribution and taxes have a positive impact, this is based from significance value of 0.003 that means the two variables have a positive impact.